A new high-Q×f Li4NbO4F microwave dielectric ceramic for LTCC applications. Issue 3 (1st February 2021) - Chu, Xin; Jiang, Juan; Wang, Jinzhao; Wu, Yuanchuang; Gan, Lin; Zhang, Tianjin
Abstract: A novel microwave dielectric ceramic material, Li4 NbO4 F, was fabricated by the solid-state reaction method. The microwave dielectric properties, sintering characteristics, and crystal structures of the Li4 NbO4 F ceramic samples were investigated. It was found that the Li4 NbO4 F ceramic samples can be successfully sintered at low temperatures (e.g., 750–875 °C). The samples exhibited a single cubic rock salt phase and possessed homogenous microstructures and outstanding microwave dielectric properties. The optimal properties of Q × f  = 61111 GHz, ε r  = 15.2, and τ ƒ  = −51 ppm/°C were achieved in the ceramic sample sintered at 825 °C. Additionally, the ceramic samples showed superior compatibility with Ag, indicating that Li4 NbO4 F is a promising low-temperature co-fired ceramic (LTCC) material.